Simultaneous operation in a patient with recurrent varicosity and recurrent inguinal hernia in a one-day hospital. Case report - A. I. Chernookov; S. I. Dolgov; S. I. Kandyba; A. M. Nikolaev; A. A. Atayan; E. O. Hachatryan (Амбулаторная хирургия, 2021)
Introduction. Currently, despite the use of modern and high-tech methods of surgical treatment of patients with varicose veins and hernias of the anterior abdominal wall in the long-term period, relapses of the disease occur in 1.7-14% of cases. The combination of postoperative recurrence of inguinal hernia and varicosis is an infrequent type of multiple surgical pathology.Case report. The article presents a clinical observation of a patient with a relapse of varicosis and an inguinal hernia, who underwent a total of three surgical interventions before admission to the clinic. Detailed ultrasound diagnostics made it possible to establish the cause of the relapse and develop optimal surgical tactics, taking into account the individual characteristics of the disease and the nature of previous operations. Taking into account the anatomical proximity and one-sided localization of pathological processes, the patient underwent a simultaneous operation from one access. A day later, the postoperative pain intensity was rated with a visual analogue scale at 4.2 scores, a patient administered analgesics to relieve pain within two postoperative days. Class 2 compression stockings were used for the compression therapy. The patient was discharged from the clinic in satisfactory condition the following day after the intervention, complaining of minor pain in the surgical wound area. The postoperative period was uneventful, without complications. Pain, restriction of movement were observed within 4 days after surgery. The sutures were removed after 7 days, the wound healed by primary intention healing.Conclusions. The use of a simultaneous operation allows a radical correction of both diseases, to reduce the psychological burden on the patient, to improve the aesthetic result of the intervention, to avoid thrombotic complications and hernia infringement in the postoperative period.